2018
DOI: 10.1016/j.jpcs.2017.11.019
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and theoretical study to explain the morphology of CaMoO 4 crystals

Abstract: Ag 2 CrO 4 microcrystals were synthesized Q3 using the co-precipitation method. These microcrystals were characterized through X-ray diffraction (XRD) with Rietveld analysis, field-emission scanning electron microscopy (FE-SEM), transmission electron microscopy (TEM) with energy-dispersive spectroscopy (EDS), micro-Raman (MR). XRD patterns and Rietveld refinement data showed that the material exhibits an orthorhombic structure without any deleterious phases. FE-SEM and TEM micrographs revealed the morphology a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 85 publications
1
27
0
Order By: Relevance
“…The observed diffraction peaks can be indexed to the CaMoO 4 scheelite type (tetragonal structure) with the space group I4 1/a and are in full agreement with the standard data (JCPDS card no. 29‐0351) 52,53 . The additional peaks were observed only in XRD pattern corresponding to the CMO:Tm‐12 sample, and they occur at 2θ = 7.8°, 23.0°, and 35.5° (Figure 1G).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The observed diffraction peaks can be indexed to the CaMoO 4 scheelite type (tetragonal structure) with the space group I4 1/a and are in full agreement with the standard data (JCPDS card no. 29‐0351) 52,53 . The additional peaks were observed only in XRD pattern corresponding to the CMO:Tm‐12 sample, and they occur at 2θ = 7.8°, 23.0°, and 35.5° (Figure 1G).…”
Section: Resultsmentioning
confidence: 97%
“…29-0351). 52,53 The additional peaks were observed only in XRD pattern corresponding to the CMO:Tm-12 sample, and they occur at 2θ = 7.8°, 23.0°, and 35.5° (Figure 1G). These peaks are predicted theoretically through simulations for a compressed and distorted CaMoO 4 tetragonal structure.…”
Section: Xrd Analysismentioning
confidence: 99%
“…Even, at biological level, the invention of DNA origami has deepened the understanding of how molecules could interact with each other in a complex self-assembly process and has accelerated the engineering of molecular systems with custom-designed structures and programmable behaviors [153][154][155][156][157][158][159] . In solid state, the concept of crystal origami has been introduced toward the rational design of surface structures of micro-and nano-crystallites 144,160,161 .…”
Section: Concept Of Surface Energymentioning
confidence: 99%
“…Among the work on phosphors with good color purity and high luminous efficiency, research intended to facilitate the use of molybdate phosphors doped with rare-earth ions in various applications, such as light-emitting devices, lasers, scintillation materials, optical fibers, catalysts, and displays, is attracting attention [ 6 , 7 , 8 ]. Specifically, calcium molybdate (CaMoO 4 ) can be used in a wide range of applications due to its stable physicochemical properties and the low absorption critical energy of its scheelite structure [ 9 , 10 ]. Kim et al produced CaMoO 4 :Eu 3+ with Na + phosphors with a diameter of 5 nm from a TOA-MoO 4 complex with calcium, europium, and sodium-oleate (Ca, Eu, and Na-oleate) mixed in toluene using a solvothermal synthesis method, and suggested that the strongest red emission occurred in Ca 0.58 MoO 4 : 0.21 Eu 3+ , with 0.21 Na + nanophosphors synthesized at 120 °C [ 11 ].…”
Section: Introductionmentioning
confidence: 99%